Critical Test of the Beneficial Consequences of Lifting the Ban on Direct-to-Consumer Advertising for Prescription Drugs in Italy: Experimental Exposure and Questionnaire Study - Peter Johannes Schulz; Francesca Crosignani; Serena Petrocchi (JMIR Publications, 2023)
BackgroundThere are only two countries in the world (the United States and New Zealand) that allow the pharmaceutical branch to advertise prescription medication directly to consumers. There is pressure on governments to allow direct-to-consumer advertising (DTCA) for prescription drugs elsewhere too. One argument the industry uses frequently is the claim that exposure to DCTA, through various methods and occasions, is supposed to improve customers' knowledge of a disease and treatment. This argument has been part of the health care community's wider discussion of whether DTCA of prescription drugs benefits the population's general interest or is only an attempt to increase the sales of the pharmaceutical branch. Belief in true learning by DTCA is rooted in concepts of empowered consumers and their autonomous and empowered decision-making. ObjectiveIn this study, we tested the hypotheses that contact with DTCA increases recipients' literacy/knowledge, especially regarding the side effects of treatment (hypothesis 1), and empowerment (hypothesis 2). We further hypothesized that DTCA exposure would not increase depression knowledge (ie, about treatments, symptoms, and prevalence) (hypothesis 3). MethodsA snowball sample of 180 participants was randomly split into three experimental groups receiving (1) a traditional information sheet, (2) a DTCA video clip for an antidepressant prescription drug, or (3) both. The video was original material from the United States translated into Italian for the experiment. Dependent variables were measures of depression knowledge (regarding treatments, symptoms and prevalence, and antidepressant side effects), depression literacy, and empowerment. ResultsNone of the experimental groups differed significantly from the others in the empowerment measure (hypothesis 2 not confirmed). Partial confirmation of hypothesis 1 was obtained. Lower values on the depression literacy scale were obtained when participants had been given the video compared to the sheet condition. However, the general depression knowledge and its subscale on side effects reached higher scores when participants were exposed to the DTCA, alone or in combination with the information sheet. Finally, participants showed lower scores on knowledge about treatment and symptoms or prevalence after watching the video compared to the sheet condition (hypothesis 3 confirmed). Symptoms and prevalence knowledge increased only when the video was presented in combination with the sheet. ConclusionsThere is no evidence for an increase in empowerment following DTCA exposure. An increase in knowledge of the side effects of the medication was observed in the group exposed to the DTCA video. This was the only result that confirmed the hypothesis of the beneficial effect of DTCA videos on knowledge. Written information proved to be the most suitable way to convey knowledge on treatments and symptoms prevalence. Our findings support the necessity of studying health literacy and patient empowerment together and the consequences of such an increase in knowledge in terms of help-seeking behavior.